The Cochrane Database of Systematic Reviews 2003
DOI: 10.1002/14651858.cd003951
|View full text |Cite
|
Sign up to set email alerts
|

Surgical versus medical treatment with cyclooxygenase inhibitors for symptomatic patent ductus arteriosus in preterm infants

Abstract: The data regarding net benefit/harm are insufficient to make a conclusion as to whether surgical ligation or medical treatment with indomethacin is preferred as initial treatment for symptomatic PDA in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
1
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 52 publications
1
75
1
10
Order By: Relevance
“…More is not better: early indomethacin is worse than later indomethacin 29 and ligation is worse than either medical therapy 29,34,35 or no treatment. 36 Pooled results from randomized-controlled trials These trials have been the subject of several Cochrane reviews, [113][114][115][116][117][118] which have found no evidence for long-term benefits of treatment to close the ductus. As the purpose of Cochrane reviews is identification of strong evidence in support of an intervention, many trials were excluded from meta-analyses because of methodological deficiencies.…”
Section: Findings From Individual Randomized-controlled Trialsmentioning
confidence: 99%
“…More is not better: early indomethacin is worse than later indomethacin 29 and ligation is worse than either medical therapy 29,34,35 or no treatment. 36 Pooled results from randomized-controlled trials These trials have been the subject of several Cochrane reviews, [113][114][115][116][117][118] which have found no evidence for long-term benefits of treatment to close the ductus. As the purpose of Cochrane reviews is identification of strong evidence in support of an intervention, many trials were excluded from meta-analyses because of methodological deficiencies.…”
Section: Findings From Individual Randomized-controlled Trialsmentioning
confidence: 99%
“…Due to reduced renal side effects compared to other drugs, ibuprofen in three consecutive doses is administrated. Although current data are insufficient to support which primary therapeutic approach should be addressed first, surgical ligation or administration of inhibitors of cyclooxygenase, our preferred first approach is drug administration [17,18]. Subsequent haemodynamic changes with decreased blood flow in the aorta required the initiation of prostaglandin E1 therapy for the reopening of the ductus arteriosus, it being necessary until the time of corrective surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, similar results have been observed with the use of ibuprofen IV; both drugs have been shown to be equally effective in ductal closure and to reduce surgical ligation rates of PAD [13][14][15] . If closure of the PAD is not achieved with one or two cycles of NSAID therapy, surgical closure is indicated 16 . More recently, paracetamol has been used, however clinical experience is still under development 17,18 .…”
Section: Introductionmentioning
confidence: 99%